2020
DOI: 10.4028/www.scientific.net/kem.838.59
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of a Combination of Recycled Rubber from Waste Tires and Waste Waters from a Concrete Plant in the Production of Cement Composites

Abstract: This article presents the results of a study dealing with the use of a combination of recycled rubber from waste tires as a 100% replacement of aggregate and waste sludge water from a concrete plant as a partial replacement of mixing water in the production of cement composites. The aggregate was replaced with recycled rubber material in two ratios. The first ratio was 50/50 and the other one was a 40/60 ratio of fraction 0/1 mm and fraction 1/3 mm. The mixing water was replaced with waste sludge water from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
0
0
1
Order By: Relevance
“…Similar to this study, Pérez-Guevara et al also confirmed the most frequent occurrence of fibers in samples of drinking water [26]. The Fibre category included particles with a length at least 3 times greater than their width.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to this study, Pérez-Guevara et al also confirmed the most frequent occurrence of fibers in samples of drinking water [26]. The Fibre category included particles with a length at least 3 times greater than their width.…”
Section: Resultssupporting
confidence: 86%
“…One effective approach involves the reutilization of macroplastics, wherein products can be meticulously recycled and upcycled. As an example, tires, which contribute significantly to secondary microplastic sources, could potentially find application in the production of cement composites [26,27]. This innovative reimagining of tire usage presents a promising avenue for curtailing the microplastic menace.…”
Section: Resultsmentioning
confidence: 99%
“…Las investigaciones más relevantes se concentran en el uso del caucho provenientes de neumáticos reciclados con la finalidad de estudiar la resistencia normal del concreto, pero hay pocos estudios disponibles que analicen el efecto de agregar caucho en el concreto de alta resistencia (Abdelmonem, El-Feky M, Nasr, & Kohail, 2019),así como pocos estudios sobre modelado y predicción de la resistencia a la compresión, las regresiones multivariables no lineales no se han utilizado hasta ahora para la predicción del comportamiento del concreto con caucho (Jalal, Nassir, Jalal, & Arabali, 2019). Su uso práctico como nuevo material en la construcción requiere de una comprensión profunda y una predicción confiable de sus efectos (Svoboda, Václavík, Dvorský, Klus, & Botula, 2020). Por lo tanto, una revisión completa actualizada sobre el concreto con caucho de neumáticos reciclados es necesaria para comprender el comportamiento de este importante material de construcción, aunque se han realizado considerables investigaciones, muchas siguen siendo controvertidas (Li, Zhang, Wang, & Dang, 2019).…”
Section: Introductionunclassified